2016
DOI: 10.1007/s00005-016-0417-7
|View full text |Cite
|
Sign up to set email alerts
|

Autoreactive IgE in Chronic Spontaneous/Idiopathic Urticaria and Basophil/Mastocyte Priming Phenomenon, as a Feature of Autoimmune Nature of the Syndrome

Abstract: Recent years of research have shed a new light on the role of IgE in immune reactions. It seems to be more than just a contribution to immediate type of allergic response. It appears that monomeric IgE may enhance mast cell activity without cross-linking of FcεRI by IgE specific allergen or autoreactive IgG anti-IgE antibodies. Monomeric IgE molecules are heterogeneous concerning their ability to induce survival and activation of mast cells only by binding the IgE to FcεRI, but not affecting degranulation of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 57 publications
0
15
0
1
Order By: Relevance
“…Actually, levels of total/specific IgE as well as expression rate of allergic diseases slightly higher than in the general population have already been reported in patients with CSU [ 56 58 ]. Moreover, the skin MC TC subset, the main actor of CSU history, largely depends on its multiple and not yet fully clarified functions by activation of FcεRI-IgE axis, among others also by auto-allergens [ 8 12 , 25 , 59 , 60 ]. This is all true considering that in experimental animal models it has elegantly been demonstrated that perivascular skin MC TC are able to exhibit a selective uptake of IgE by their positioning and by extending a cell process across the vessel wall to capture intraluminal IgE [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Actually, levels of total/specific IgE as well as expression rate of allergic diseases slightly higher than in the general population have already been reported in patients with CSU [ 56 58 ]. Moreover, the skin MC TC subset, the main actor of CSU history, largely depends on its multiple and not yet fully clarified functions by activation of FcεRI-IgE axis, among others also by auto-allergens [ 8 12 , 25 , 59 , 60 ]. This is all true considering that in experimental animal models it has elegantly been demonstrated that perivascular skin MC TC are able to exhibit a selective uptake of IgE by their positioning and by extending a cell process across the vessel wall to capture intraluminal IgE [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although the pathophysiology of CSU is not yet completely understood, a strong characteristic of the disease is the specific increased activation and/or degranulation of skin mast cells (MCs). These are primed to increase the release of proinflammatory and vasoactive mediators through different immunological or non-immunological stimuli and synergistic/sequential different pathomechanisms [ 6 – 12 ]. Over the past five years, clinical studies have demonstrated the efficacy and safety of the monoclonal antibody omalizumab in the treatment of spontaneous and inducible chronic urticaria [ 13 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…If the followed eradication decrease the symptoms again – the HP diagnosis and eradication can be considered as add-on therapy to standard chronic urticaria diagnosis and treatment. Recently emerging mastocyte/basophil priming phenomenon, as a feature of CIU and consequence of autoreactive IgE against several HP internal factors may provide a new insight into pathogenesis of this complex syndrome [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…По мере увеличения антигенной нагрузки (при более выраженном воспалительном повреждении ткани) иммунный ответ переключается на IgG. Данные о том, что IgE-аутоантитела, включая sIgE к ТПО, могут индуцировать симптомы ХСК, подтверждаются активацией тучных клеток и базофилов [10,13,14], а также эффективностью терапии омализумабом у пациентов с ХСК [9].…”
Section: р е з у л ьт а т ы и о б с у ж д е н и еunclassified